Secretary of the English philosopher Bertrand Russell and Secretary-General of the Vietnam Tribunal at Paris - Hoeneveld, Herman,
Secretary of the English philosopher Bertrand Russell and Secretary-General of the Vietnam Tribunal at Paris.